Conflict and COVID-19 in Yemen: beyond the humanitarian crisis - Mohammed Alsabri; Ayman Alhadheri; Luai M. Alsakkaf; Jennifer Cole (BMC, 2021)
Abstract Background Yemen has been left in shambles and almost destroyed by its devastating civil war, and is now having to deal with the spread of coronavirus. The Yemeni people have been are left to fend for themselves and faced many problems such as hunger, the ongoing war, infections, diseases and lack of equipment even before the COVID-19 pandemic. All together it is a humanitarian crisis. Only around 50% of the hospitals and healthcare facilities are in full working condition, and even those that are functioning are operating at nowhere near full potential. Healthcare staff and facilities lack necessary essential equipment and money. Conclusion As, sadly, is common in conflict-affected regions, the violence has brought with it a secondary disaster of infectious disease outbreaks. Yemen is not only battling COVID-19 amid a catastrophic war, but also has to deal with other diseases such as cholera, diphtheria and measles. A number of key measures are needed to support the current efforts against this deadly epidemic and its potential subsequent waves as well as to prevent further epidemics in Yemen.